Activity Budget and Diet in Sumatran Orangutan (Pongo abelii) at Soraya Research Station, Aceh - Mahyana; Kanthi Arum Widayati; Puji Rianti (HAYATI Journal of Biosciences, 2023)
Geographical and environmental factors influence the food availability and diet of orangutans. Moreover, tree phenology affects productivity and food availability in orangutan habitats. As a result, orangutans must be able to adapt to their food availability in the wild. This study aims to analyse the daily activity patterns and eating behaviour of the Sumatran orangutan (Pongo abelii) and their relationship to food availability through the fruit availability index (FAI) and phenology at Soraya Research Station (SRS), Aceh. From the 648 hours of observation on five orangutans' daily activities, we found that resting is the activity with the highest percentage (48%), followed by feeding (22.5%) and moving (21.8%). The high percentage of resting activity might correlate with its low FAI in SRS (1.01%). The resting activity limits orangutans' energy expenditure. Furthermore, barks, fruits, and other plants (including lianas, ferns, and epiphytes) were the main type of diet of Sumatran orangutans in SRS with a frequency of 40.6%, 28.9%, and 15.6%, respectively. The high bark consumption by the orangutans acts as their fallback diet at SRS and is thought to be a form of adaptation to the low fruit availability. This study showed the orangutan adaptation to low fruit availability in SRS through their daily activity and diet patterns.